2005
DOI: 10.1177/1078087405280311
|View full text |Cite
|
Sign up to set email alerts
|

Voting for Minority Candidates in Multiracial/Multiethnic Communities

Abstract: Recent research suggests that over time the performance of minority officeholders rivals racebased attitudes and group membership as the primary determinant of citizen evaluations of minority officeholders. Here, we examine the determinants of electoral support for an AfricanAmerican mayor in a multiracial/multiethnic venue. We test alternative explanations (race, social distance, and performance-based models) of voter support for an African-American mayor in a setting where no ethnic or racial group represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 14 publications
1
26
0
Order By: Relevance
“…Arceneaux (2005) finds that survey respondents connect their evaluation of mayors' performance on traffic congestion and other salient issues to their vote choice. Finally, Stein, Ulbig, and Post (2005) find that mayoral approval significantly predicts vote choice in several recent Houston mayoral elections. Finally, Stein, Ulbig, and Post (2005) find that mayoral approval significantly predicts vote choice in several recent Houston mayoral elections.…”
Section: Responsiveness In City Governmentmentioning
confidence: 82%
“…Arceneaux (2005) finds that survey respondents connect their evaluation of mayors' performance on traffic congestion and other salient issues to their vote choice. Finally, Stein, Ulbig, and Post (2005) find that mayoral approval significantly predicts vote choice in several recent Houston mayoral elections. Finally, Stein, Ulbig, and Post (2005) find that mayoral approval significantly predicts vote choice in several recent Houston mayoral elections.…”
Section: Responsiveness In City Governmentmentioning
confidence: 82%
“…Given recent evidence showing that performance now rivals race when it comes to evaluating black mayors' performance while in office (Howell and Perry 2004; Stein, Ulbig, and Post 2004), this latter finding may not be altogether surprising. However, the present study demonstrates this confluence of representational and policy effects more systematically than perhaps has been the case thus far.…”
Section: Discussionmentioning
confidence: 90%
“…For instance, the elevated expectations and enhanced feelings of empowerment blacks typically feel upon the election of African American officials may be replaced with feelings of alienation if these officials do not take actions that respond to black constituents' needs (see Bobo and Gilliam 1990; Tate 2003). Indeed, a handful of recent studies show that performance has come to rival race‐based attitudes and group membership as the key determinant of both citizen evaluations of minority officeholders (Hajnal 2001; Howell and McLean 2001; Howell and Perry 2004) and these elected officials' chances of reelection (Stein, Ulbig, and Post 2004). Thus further empirical tests are needed in order to more fully explore whether representation‐fueled attitudinal effects are driven by racial empathy alone or whether government outputs—what black elected officials do when in office—matter as well.…”
Section: Conceptualizing and Analyzing Black Political Incorporationmentioning
confidence: 99%
“…Viable Black candidates often have to compete with White opponents in attracting White voters' support in order to win U.S. elections. Thus, the willingness of Whites to vote for Black candidates has drawn considerable attention from students of racial politics (Carsey 1995 ;Gillespie 2012 ;Hajnal 2007 ;King and Smith, 2008 ;Kraus and Swanstrom, 2005 ;Liu 2006 ;Lublin 1997 ;Stein et al, 2005 ). It has been found that Americans often cast their votes along racial lines (Barreto 2007 ;Dawson 1994 ;Gay 2004 ;Kinder and Sanders, 1996 ;Liu and Vanderleeuw, 2007 ).…”
Section: State Context and White Votingmentioning
confidence: 99%